Categorisation of Tweets Using Ensemble Classification Methods - Mohanavalli, S; Karthika, S; ., Srividya; R.Uthayan, K; Sandya, N (International Journal of Engineering and Technology, 2018)
Twitter is a micro-blogging site that facilitates users to exchange short messages. Twitter is predominantly used in fields like business, healthcare, education and nation security. Twitter is being used by a large number of users for updating real time information and sentiment expression. The objective of this paper is to automate the classification of tweets into particular category using various machine learning algorithms like naÃ¯ve bayes, SVM, and linear regression model. The proposed ensemble model aims to improve performance metrics of these algorithms. A comparative study of the algorithms used for tweet classification is done and results are discussed in the paper. Â Â